The conventional management of periapical cyst caused by post-dental treatment failure: A case report - Florence Ariyana Manuputty; Sylvyana M; Tasman A (Intisari Sains Medis, 2018)
Background: Periapical cyst is the typical type of cyst that found in dental practices. Periapical cyst is an advanced phase of dental infection due to caries. Untreated caries will leads to pulpitis and develop to pulp necrosis. Periapical cyst is formed following the necrotic pulp. This study aims to describe the conventional management by enucleation technique to periapical cyst due to post-dental treatment failure.Case Description: A 22-years-old female patient came to oral and maxillofacial surgery clinic with a chief complaint of palatal swelling since eight months ago. On clinical examination, there was palatal swelling of 2x1x1 cm in size and radiograph showed a periapical cyst about pulp gangrene of teeth 21 and 22. Trauma history was found about 5 years ago with anterior teeth fractured and treated with restoration. The cyst was treated by enucleation and extraction was carried out for pulp gangrene teeth. There was no obturator insertion. The treatment showed a good prognosis and no secondary infection noticed.Conclusion: The treatment of periapical cyst was successfully by non-surgery conventional therapy with endodontic treatment and surgery method by enucleation for the bigger lesion. Cyst enucleation can be done without any complication, such as periodontal tissue damage.